Hydrophobin-Coated Perfluorocarbon Microbubbles with Strong Non-Linear Acoustic Response - Valentina Dichiarante; Giuseppina Salzano; Philippe Bussat; Emmanuel Gaud; Samir Cherkaoui; Pierangelo Metrangolo (Chemistry, 2024)
Gas-filled microbubbles are well-established contrast agents for ultrasound imaging and widely studied as delivery systems for theranostics. Herein, we have demonstrated the promising potential of the hydrophobin HFBII—a fungal amphiphilic protein—in stabilizing microbubbles with various fluorinated core gases. A thorough screening of several experimental parameters was performed to find the optimized conditions regarding the preparation technique, type of core gas, HFBII initial concentration, and protein dissolution procedure. The best results were obtained by combining perfluorobutane (C4F10) gas with 1 mg/mL of aqueous HFBII, which afforded a total bubble concentration higher than 109 bubbles/mL, with long-term stability in solution (at least 3 h). Acoustic characterization of such microbubbles in the typical ultrasound frequency range used for diagnostic imaging showed the lower pressure resistance of HFBII microbubbles, if compared to conventional ones stabilized by phospholipid shells, but, at the same time, revealed strong non-linear behavior, with a significant harmonic response already at low acoustic pressures. These findings suggest the possibility of further improving the performance of HFBII-coated perfluorinated gas microbubbles, for instance by mixing the protein with other stabilizing agents, e.g., phospholipids, in order to tune the viscoelastic properties of the outer shell.